A survey on ethnoveterinary medicines used by the tribal migratory shepherds of Northwestern Himalaya. (5th October 2022) - Radha,; Prakash, Suraj; Sharma, Niharika; Kumar, Amit; Kumari, Neeraj; Puri, Sunil; Pundir, Ashok; Kumar, Vijay; Sharma, Abhishek Kumar; Rais, Nadeem; Dey, Abhijit; Lorenzo, José M.; et al.
Abstract: Ethnopharmacological relevance: Tribal migratory shepherds (Gaddi) living in the Northwestern Himalayan region are well known for their nomadic lifestyle in which tribal migratory shepherds along with their livestock which mainly include sheep and goat migrate seasonally in the Northwestern Himalayan region from high hills to low hills for the survival of their livestock from cold winters and hot summer. Due to harsh environmental conditions, heavy snowfall, heavy rainfall, wild animal attacks, no medical facilities, no transportation, and no electricity facilities tribal migratory shepherds mostly rely on plant species mentioned for ethnoveterinary use to treat livestock disease. Aim of study: The aim of our study is to conduct ethnoveterinary survey for the first time to document the contemporary oral ethnoveterinary knowledge of Gaddi shepherds living in Northwestern Himalayan region. Methodology: The documentation of plant species mentioned for ethnoveterinary use was executed through extensive field surveys from 2017 to 2019. Data were collected through direct interviews by administrating questionnaire among tribal migratory shepherds. Results: A total of 181 plant species mentioned for ethnoveterinary use belonging to the same or different families were documented during the seasonal migration of shepherds from Northwestern Himalayan region. Most frequently occurring family of plant species mentioned for ethnoveterinary was Poaceae, leaves and roots were reported to be the most frequently used plant parts. Most frequently documented plant species for ethnoveterinary use were Cynodon dactylon, Chenopodium album, Zanthoxylum armatum, Aloe vera, Azadirachta indica and Cannabis sativa . Chrysopogon serrulatus, Cynodon dactylon, and Vitex negundo were reported with high use reports. Some of the endemic species of Northwestern Himalayan region such as Elymus himalayanus and Euphorbia pilosa and one endangered species Picrorhiza kurrooa were reported in current study. Conclusion: It is observed that there is a need to raise awareness among the tribal migratory shepherds about the sustainable use and conservation of some of the plant species mentioned for ethnoveterinary use. This study provided an inventory of plant species mentioned for ethnoveterinary use having significant ethnoveterinary potential, however there is need of scientific evaluations by in vitro, in vivo and clinical studies. Graphical abstract: Image 1